Effect of Different Roasting Levels and Manual Brewing Techniques on the Sensory Profile of Liberica Coffee with Honey Process - Sunarharum, Wenny Bekti; Nurminah, Mimi; Purba, Newyearta Gloria (Journal of Coffee and Sustainability, 2024)
Liberica coffee is less popular than Arabica and Robusta coffees. One reason is that Liberica coffee has a less pleasant flavor than its other counterparts. Exploration on Liberica coffees and the processing impact on quality is still limitedly published. The objectives of this research are to evaluate the effect of different roasting levels and manual brewing techniques on the sensory profile of Liberica coffee. The green coffee beans used in this study are processed using honey.  The Qualitative Descriptive Analysis (QDA) method evaluated sensory profiles, while a preference test was also performed.  The brewed coffee’s basic physicochemical characteristics (color, pH, and Total Dissolved Solids (TDS)) were measured. The sensory evaluation applied a factorial Randomized Block Design with two factors, i.e., roasting level (light, medium, dark) and manual brewing technique (V60, French press), while the physicochemical characteristics analysis followed a nested design. The results showed that different roasting levels and manual brewing techniques significantly impacted 11 coffee sensory attributes, pH values, and panelists' preferences. The most preferred Liberica coffee honey processing treatment was light roast level with the V60 manual brewing technique.